(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article focuses on the role of professional reflection in the formation of professional training in future teachers. In particular, the essence of professional training in the personality of a future teacher and the content of approaches in this area were analyzed. At the same time, the relationship between professional training and professional reflection in the personality of a future teacher was investigated.